Prognostic and Clinicopathological Significance of E-Cadherin in Pancreatic Cancer Patients: A Meta-Analysis - Wang, Pengbo; Zhu, Zengkuan (Frontiers in Oncology, 2021)
Background: Several recent studies have investigated the prognostic and clinicopathological significance of epithelial cadherin (E-cadherin) in pancreatic cancer; however, conclusions from these studies remain inconsistent. Therefore, we performed a meta-analysis to evaluate the effects of E-cadherin expression on the prognosis and clinicopathological characteristics of pancreatic cancer. Methods: Embase, PubMed, and Web of Science were searched to identify articles associated with E-cadherin and pancreatic cancer. Hazard ratios (HRs) and odds ratios (ORs) with corresponding confidence intervals (CIs) were calculated and summarized. All eligible studies were searched until May 20, 2020. Heterogeneity among studies was assessed using the Chi-square test and I2 statistic. Results: Overall, 25 studies were identified, of which 12 reports with 1,032 cases concerned the prognosis of pancreatic cancer, and 22 involved the risk and clinical characteristics of pancreatic cancer. The overall results revealed that E-cadherin expression was significantly related to overall survival, gender, tumor grade, lymph node metastasis, tumor differentiation, and risk of pancreatic cancer. In the subgroup analysis, no significant heterogeneity or publication bias was observed. Conclusions: E-cadherin expression is strongly associated with the risk, clinical features, and prognosis of pancreatic cancer, suggesting that E-cadherin may be an effective biomarker for the early detection of pancreatic cancer.